Tempat Perkembangbiakan Nyamuk Aedes spp. Di Pasar Wisata Pangandaran - Joni Hendri; roy Nusa RES; Heni Prasetyowati (Loka Litbang Kesehatan Pangandaran, 2010)
An observation of Aedes spp. breeding places in water container was carried out located at Pasar Wisata Pangandaran. The final results showed that larvae were found mostly in bucket (28,21 %), container with plastic based goods (87,18 %) and container with blue colors(33,33%). The House Index (HI) rate was 29,20 %, Container Index (CI) rate was 9,30 %, Breteau Index (BI) rate was 40,6. The research to, showed the barrels or drum was been most productive container with Pupae Index (PI) rate was 25,42.